2022
DOI: 10.1002/jum.16039
|View full text |Cite
|
Sign up to set email alerts
|

Blood Flow Turbulence Quantification of Carotid Artery With a High‐Frame Rate Vector Flow Imaging

Abstract: Objectives To assess the feasibility and performance of Turbulence (Tur) index as a quantitative tool for carotid artery flow turbulence; to detect and compare the blood flow patterns of common carotid artery (CCA) and carotid bulb (CB) at different ages and cardiac phases in healthy adults, and thus interpret the evolvement of etiology difference between CCA and CB. Methods Carotid flow characteristics of 40 healthy volunteers were evaluated quantitatively by a high‐frame rate vector flow imaging. Three types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…A previous study ( 36 ) demonstrated that flows with Tur value < 1% can be considered laminar or nearly laminar flow. Another recent study ( 40 ) presented the Tur difference between common carotid artery and carotid bulb. In both two studies, it can be seen that quantification for the flow turbulence using Tur index to distinguish laminar and non-laminar flows is not a linear variation trend since for non-laminar flows Tur values range from 1 to 100%, which is much greater than the laminar flow range of 0 to 1%.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study ( 36 ) demonstrated that flows with Tur value < 1% can be considered laminar or nearly laminar flow. Another recent study ( 40 ) presented the Tur difference between common carotid artery and carotid bulb. In both two studies, it can be seen that quantification for the flow turbulence using Tur index to distinguish laminar and non-laminar flows is not a linear variation trend since for non-laminar flows Tur values range from 1 to 100%, which is much greater than the laminar flow range of 0 to 1%.…”
Section: Discussionmentioning
confidence: 99%
“…Our study confirmed the effectiveness of HiFR‐VFI in this regard with similar results to recently published studies. This indicates that HiFR‐VFI is more precise and less angle‐ and operator‐dependent for in‐vivo estimation than conventional CDFI ultrasound 20,29 …”
Section: Discussionmentioning
confidence: 93%
“…Previous studies have demonstrated that blood flow occurs in the descending systole phase in a large momentum state, and turbulent phenomena, such as vortices, are more evident 20,22 . Therefore, this study only discussed the blood flow patterns in the systole phase.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations